2023
DOI: 10.1038/s41398-023-02534-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic, long-term effects of glutamate dehydrogenase 1 deficiency and mild stress on cognitive function and mPFC gene and miRNA expression

Abstract: Glutamate abnormalities in the medial prefrontal cortex (mPFC) are associated with cognitive deficits. We previously showed that homozygous deletion of CNS glutamate dehydrogenase 1 (Glud1), a metabolic enzyme critical for glutamate metabolism, leads to schizophrenia-like behavioral abnormalities and increased mPFC glutamate; mice heterozygous for CNS Glud1 deletion (C-Glud1+/− mice) showed no cognitive or molecular abnormalities. Here, we examined the protracted behavioral and molecular effects of mild inject… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Research by Virmani et al [ 45 ] suggests that the activity of the CPT system (CPT1 and CPT2) is associated with Parkinson’s disease, Alzheimer’s disease, and schizophrenia, mainly related to changes in insulin balance in the brain. GLUD1 in the central nervous system is a crucial metabolic enzyme in glutamate metabolism and can lead to behavioral abnormalities and increased mPFC glutamate in schizophrenia patients [ 46 ]. Research by Yadav et al [ 47 ] found that the absence of GLUD1 leads to abnormal emotional and social behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Virmani et al [ 45 ] suggests that the activity of the CPT system (CPT1 and CPT2) is associated with Parkinson’s disease, Alzheimer’s disease, and schizophrenia, mainly related to changes in insulin balance in the brain. GLUD1 in the central nervous system is a crucial metabolic enzyme in glutamate metabolism and can lead to behavioral abnormalities and increased mPFC glutamate in schizophrenia patients [ 46 ]. Research by Yadav et al [ 47 ] found that the absence of GLUD1 leads to abnormal emotional and social behavior.…”
Section: Discussionmentioning
confidence: 99%
“…3g). These genes include known stress-related genes such as Cldn11, Vamp1, Glud1 and Etnppl [44][45][46][47]. For all of the overlapped genes, fold change is bigger for SLAM-seq analysis than RNA-seq (Fig.…”
Section: Sensitivity Of Slam-seq Vs Rna-seqmentioning
confidence: 99%